Abnormal Resting-State Functional Connectivity in Progressive Supranuclear Palsy and Corticobasal Syndrome - Bharti, Komal; Bologna, Matteo; Upadhyay, Neeraj; Piattella, Maria Cristina; Suppa, Antonio; Petsas, Nikolaos; Giannì, Costanza; Tona, Francesca; Berardelli, Alfredo; Pantano, Patrizia (Frontiers in Neurology, 2017)
Background: Pathological and MRI-based evidence suggests that multiple brain structures are likely to be involved in functional disconnection between brain areas. Few studies have investigated resting-state functional connectivity (rsFC) in progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS). In this study, we investigated within- and between-network rsFC abnormalities in these two conditions. Methods: Twenty patients with PSP, eleven patients with CBS and sixteen healthy subjects (HS) underwent a resting-state fMRI study. Resting-state networks (RSNs) were extracted to evaluate within- and between-network rsFC using the Melodic and FSLNets software packages. Results: Increased within-network rsFC was observed in both PSP and CBS patients, with a larger number of RSNs being involved in CBS. Within-network cerebellar rsFC positively correlated with mini mental state examination scores in patients with PSP. Compared to healthy volunteers, PSP and CBS patients exhibit reduced functional connectivity between the lateral visual and auditory RSNs, with PSP patients additionally showing lower functional connectivity between the cerebellar and insular RSNs. Moreover, rsFC between the salience and executive control RSNs was increased in patients with CBS compared to healthy subjects. Conclusion: This study provides evidence of functional brain reorganisation in both PSP and CBS. Increased within-network rsFC could represent a higher degree of synchronisation in damaged brain areas, while between-network rsFC abnormalities may mainly reflect degeneration of long-range white matter fibres.